2016
DOI: 10.18632/oncotarget.10432
|View full text |Cite
|
Sign up to set email alerts
|

Integrated omics-analysis reveals Wnt-mediated NAD+ metabolic reprogramming in cancer stem-like cells

Abstract: Abnormal tumor cell metabolism is a consequence of alterations in signaling pathways that provide critical selective advantage to cancer cells. However, a systematic characterization of the metabolic and signaling pathways altered in cancer stem-like cells (CSCs) is currently lacking. Using nuclear magnetic resonance and mass spectrometry, we profiled the whole-cell metabolites of a pair of parental (P-231) and stem-like cancer cells (S-231), and then integrated with whole transcriptome profiles. We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…For instance, it has been recently demonstrated that some pluripotency genes like NANOG trigger CSC maintenance and promote tumorigenicity in vivo by inducing a functional reprogramming of mitochondrial metabolism in HCC [ 116 ]. Lee et al [ 117 ] recently shaped the oncometabolites and transcriptomic profile of breast cancer stem-like cells, and found that the Wnt pathway regulates nicotinic acid adenine dinucleotide phosphate (NAADP) levels, which in turn promote CSC survival. In addition, non-codifying genomic sequences may be implicated in CSC action, as demonstrated by the evidence that an miR-122-mediated regulation of the glycolytic enzyme PK4 inhibits stem phenotypes in CD133 (+) HCC cells [ 118 ].…”
Section: Cscs At the Origin Of Cancer: What When Where And Why?mentioning
confidence: 99%
“…For instance, it has been recently demonstrated that some pluripotency genes like NANOG trigger CSC maintenance and promote tumorigenicity in vivo by inducing a functional reprogramming of mitochondrial metabolism in HCC [ 116 ]. Lee et al [ 117 ] recently shaped the oncometabolites and transcriptomic profile of breast cancer stem-like cells, and found that the Wnt pathway regulates nicotinic acid adenine dinucleotide phosphate (NAADP) levels, which in turn promote CSC survival. In addition, non-codifying genomic sequences may be implicated in CSC action, as demonstrated by the evidence that an miR-122-mediated regulation of the glycolytic enzyme PK4 inhibits stem phenotypes in CD133 (+) HCC cells [ 118 ].…”
Section: Cscs At the Origin Of Cancer: What When Where And Why?mentioning
confidence: 99%
“…Previously, we demonstrated that chronic metabolic stress induced the emergence of CSCs through reprogrammed Wnt signaling (5). Notably, these CSCs exhibited resistance to glucose deprivation-induced apoptosis by altering NAD þ metabolism, which is mechanistically related to Ca 2þ signaling (6).…”
Section: Introductionmentioning
confidence: 93%
“…OXPHOS inhibitors are emerging as promising therapeutics of malignant cancers marked by increased mitochondrial respiration (Wolf 2014 ). Antidiabetic biguanides, metformin and phenformin, have been rediscovered as OXPHOS inhibitors, and their anti-cancer effects have been proven in epidemiological, preclinical, and clinical studies (Lee et al 2016c ). Notably, metformin demonstrated selective efficacy against CSCs, sensitizing them to conventional treatments (Hirsch et al 2009 ).…”
Section: Therapeutic Exploitation Of Mitochondrial Bioenergetics In Omentioning
confidence: 99%